Synthesis and characterization of biogenic selenium nanoparticles with antimicrobial properties made by Staphylococcus aureus, methicillin‐resistant Staphylococcus aureus (MRSA), Escherichia coli, and Pseudomonas aeruginosa - Medina Cruz, David; Mi, Gujie; Webster, Thomas J. (Journal of biomedical materials research. Part A, 2018)
Antimicrobial resistance is a global concern that affects more than two million people each year. Therefore, new approaches to kill bacteria are needed. One of the most promising methodologies may come from metallic nanoparticles, since bacteria may not develop a resistance to these nanostructures as they do for antibiotics. While metallic nanoparticle synthesis methods have been well studied, they are often accompanied by significant drawbacks such as cost, extreme processing conditions, and toxic waste production since they use harsh chemicals such as corrosive agents (hydrazine) or strong acids (hydrochloride acid). In this work, we explored the environmentally safe synthesis of selenium nanoparticles, which have shown promise in killing bacteria. Using Escherichia coli, Pseudomonas aeruginosa, Methicillin‐resistance Staphylococcus aureus, and S. aureus, 90–150 nm average diameter selenium nanoparticles were synthesized using an environmentally safe approach. Nanoparticles were characterized using transmission electron microscopy, energy dispersive X‐ray spectroscopy to determine the chemical composition, and inductively coupled plasma mass spectrometry to validate chemistry. Nanoparticles were also characterized and tested for their ability to inhibit bacterial growth. A decay in bacterial growth after 24 h was achieved against both S. aureus and E. coli at biogenic selenium nanoparticle concentrations from 25 to 250 µg/mL and showed no significant cytotoxicity effect against human dermal fibroblasts for 24 h. Bacteria were able to synthesize selenium nanoparticles through the use of different functional structures within the organisms, mainly enzymes such as selenite reductases. Therefore, biogenic selenium nanoparticles made by bacteria represent a viable approach to reduce bacteria growth without antibiotics overcoming the drawbacks of synthetic methods that employ toxic chemicals. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1400–1412, 2018.